Downregulation of Akt2 attenuates ER stress-induced cytotoxicity through JNK-Wnt pathway in cardiomyocytes. Issue 3 (1st February 2018) - Gao, Yan-Xia; He, Wen-Ting; Pan, Long-Fei; Feng, Hui; Sun, Jiang-Li; Zhang, Bin; Yu, Lei; Li, Li-Jun
Graphical abstract: Abstract: Akt, also known as protein kinase B (PKB), is a serine/threonine kinase that promotes survival and growth in response to extracellular signals. Akt1 has been demonstrated to play vital roles in cardiovascular diseases, but the role of Akt2 in cardiomyocytes is not fully understood. This study investigated the effect of Akt2 knockdown on tunicamycin (TM)-induced cytotoxicity in cardiomyocytes and the underlying mechanisms with a focus on the JNK-Wnt pathway. TM treatment significantly increased the expression of Akt2 at both mRNA and protein levels, which was shown to be mediated by the induction of reactive oxygen species (ROS). Knockdown of Akt2 expression via siRNA transfection markedly increased cell viability, decreased lactate dehydrogenase (LDH) release and reduced cell apoptosis after TM exposure. The results of western blot showed that downregulation of Akt2 also attenuated the TM-induced activation of the unfolded protein response (UPR) factors and ER stress associated pro-apoptotic proteins. In addition, Si-Akt2 transfection partially prevented the TM-induced decrease in nuclear localization of β-catenin. By using the selective inhibitor SP-600, 125 to inhibit JNK phosphorylation, we found that knockdown of Akt2-induced protection and inhibition of ER stress was mediated by reversing TM-induced decrease of Wnt through the JNK pathway. In summary, these data suggested that Akt2 play a pivotal role in regulating cardiomyocyte survival during ER stress by modulating the JNK-Wnt pathway.